Body composition in high-level female rhythmic gymnasts of different age categories - Purenovic-Ivanovic, T.; Popovic, R.; Bubanj, S.; Stankovic, R. (Science & Sports, 2019)
Objectives: The objectives of the research were to establish body composition profile in female rhythmic gymnasts of different age categories so as to test and/or determine the possibility of predicting success in Rhythmic Gymnastics performance on the basis of gymnasts` body composition parameters. Materials and methods: Eighty-four elite and sub-elite female rhythmic gymnasts (age: 12.9±3.1 years, body height: 152.5±14.6cm, body mass: 40.6±12.2kg), distributed in five age categories (10 beginners, aged 7-9 years; 22 intermediate, aged 9-12 years; 18 advanced, aged 12-14 years; 19 juniors, aged 14-16 years; 15 seniors, aged 16 years and older), volunteered to participate in the study. Their baseline characteristics (age, body height, body mass, body mass index, years of training experience, Success) were established, as well as their body composition profile (body fat, muscle mass and skeletal mass percentage). Results: By means of multiple regression analysis the body composition profile's statistically significant influence on Success was established only in the group of junior and intermediate gymnasts (p<0.03 and p<0.004, respectively), with explanation of 46%, i.e. 51% of Success in Rhythmic gymnastics. Also, Regression analysis emphasized the significant independent contributions, to the prediction of the dependent variable, of two independent variables: skeletal mass percentage (juniors: p=0.02, and intermediate RGs: p=0.005) and muscle mass percentage (intermediate RGs: p=0.03), with negative relationship among these independent variables and the dependent one.